Static elasticity of cordierite I: effect of heavy ion irradiation on the compressibility of hydrous cordierite - Miletich-Pawliczek, Ronald; Scheidl, Katharina Sarah; Schmitt, M.; Moissl-Blanke, Angela P.; Pippinger, Thomas; Gatta, G. Diego; Schuster, Beatrice; Trautmann, Christina (Physics and chemistry of minerals, 2014)
The effect of ion beam irradiations on the elastic properties of hydrous cordierite was investigated by means of Raman and X-ray diffraction experiments. Oriented single crystals were exposed to swift heavy ions (Au, Bi) of various specific energies (10.0-11.1 MeV/u and 80 MeV/u), applying fluences up to 5 × 1013 ions/cm2. The determination of unit-cell constants yields a volume strain of 3.4 × 10−3 up to the maximum fluence, which corresponds to a compression of non-irradiated cordierite at ~480 ± 10 MPa. The unit-cell contraction is anisotropic (e1 = 1.4 ± 0.1 × 10−3, e2 = 1.5 ± 0.1 × 10−3, and e3 = 7 ± 1 × 10−4) with the c-axis to shrink only half as much as the axes within the ab-plane. The lattice elasticity for irradiated cordierite (ϕ = 1 × 1012 ions/cm2) was determined from single-crystal XRD measurements in the diamond anvil cell. The fitted third-order Birch-Murnaghan equation-of-state parameters of irradiated cordierite (V0 = 1548.41 ± 0.16 Å3, K0 = 117.1 ± 1.1 GPa, ∂K/∂P = −0.6 ± 0.3) reveal a 10-11 % higher compressibility compared to non-irradiated cordierite. While the higher compressibility is attributed to the previously reported irradiation-induced loss of extra-framework H2O, the anomalous elasticity as expressed by elastic softening (βa−1, βb−1, βc−1 = 397 ± 9, 395 ± 28, 308 ± 11 GPa, ∂(β−1)/∂P = −4.5 ± 2.7, −6.6 ± 8.4, −5.4 ± 3.0) appears to be related to the framework stability and to be independent of the water content in the channels and thus of the ion beam exposure.